Handbook of research on distributed medical informatics and e-health - Lazakidou, Athina A.; Siassiakos, Konstantinos M. (Medical Information Science Reference, 2009)
"This book provides a compendium of terms, definitions and explanations of concepts, processes and acronyms related to different areas, issues and trends in Distributed Medical Informatics, E-Health and M-Health"--Provided by publisher